Simulation analysis of traffic signal control and transit signal priority strategies under Arterial Coordination Conditions. (January 2019) - Mei, Zhenyu; Tan, Zhen; Zhang, Wei; Wang, Dianhai
This paper presents the findings of a simulation study evaluating the potential benefits of implementing transit signal priority (TSP) combined with arterial signal coordination for an isolated intersection. Traffic signal coordination is usually implemented along corridors with bus lanes. Active transit signal priority (active TSP) is a traffic-responsive control that prioritizes transit vehicles at signalized intersections. Thus, implementing active TSP under a stable cycle length is necessary to meet the relative demand of the non-priority phase and to maintain system stability. A real key intersection on an artery is taken as the object, and TSP controlling logics with specific restrictions are realized by using the VISSIM vehicle actuated programming module. Simulation analysis reveals the effect of TSP strategies with flow variation on the optimal cycle, and also identifies a reasonable method for selecting the gap time and initial green time of the priority phase. Results show that under special flow combination, increasing the cycle time generated by the traditional transportation and road research laboratory approach can give rise to additional benefits. The volume influences both the gap time and initial green time of the TSP phase. Moreover, the efficiency of red truncation is slightly better than that of the green extension strategy.